PENGARUH MOTIVASI DAN KEPEMIMPINAN TERHADAP KINERJA PEGAWAI KOPERASI BERINGIN JAYA PALEMBANG - Salman . (JURNAL KOMPETITIF, 2014)
"The Effect of Motivation and Leadership Against Employee Performance Cooperative Beringin Jaya Palembang " The purpose of the research conducted to find out and prove : 1 ) The effect of motivation and leadership together on Employee Performance Cooperative Beringin Jaya Palembang 2 ) The effect of motivation on employeeÃ‚Â  performanceÃ‚Â  CooperativesÃ‚Â  BeringinÃ‚Â  Jaya Palembang 3 ) Effect of Leadership on Employee Performance Cooperative Beringin Jaya Palembang . The calculations show that the regression coefficient for the variable Motivation ( X1 ) 0.173 , Leadership ( X2 ) 0.376 , and also produces a constant value of 23.916 so that multiple regression equation of this study are as follows : Y = 23.916 + 0.173 X1 + 0.376 X2 + e means constant for 23.916 states that if you ignore the Motivation and Leadership Performance score is 23.916 . Regression coefficient of 0.173 X1 states that each additional ( for + sign ) one unit scores Motivation ( X1 ) will improve performance score of 0.173 to keep the score Leadership ( X2 ) constant . X2 regression coefficient of 0, 376 states that any additions ( due to the + sign ) one unit of Leadership scoreÃ‚Â  ( X2 ) will improve performance score of 0.376 to keep the motivation score ( X1 ) constant. There is also a correlation coefficient of 0.676 and Koefien of determination ( R2 ) is 0.457 . This means that 45.7 % variation in the value of the variable performance score can be explained jointly by Motivation and Leadership in the regression model. The remaining 54.3 %Ã‚Â  is explained by other variables ( e )Ã‚Â  among others, Oversight, workculture, workenvironment,discipline, communication.Test results hypothesis test F above can be seen that the F value is 13.052 and 0.000 sig . From the mean value of the significance level sig < 0.05 which means that there is an influence motivation and leadership together to Performance . Of Linear Regression Analysis table it can be seen that the value for the variable sig Motivation is 0.036 , the mean value of the significance level sig < 0.05 which means that there is an influence on the Performance Motivation and Leadership sig for variables is 0.000 , the mean value of the significance level sig < 0.05, which means there is a leadership influence on performance . Ã‚Â Keywords : Motivation , Leadership , PerformanceÃ‚Â Ã‚Â